1996
DOI: 10.1007/bf02520009
|View full text |Cite
|
Sign up to set email alerts
|

Finite-element models of the human head

Abstract: A review is presented of the existing finite-element (FE) models for the biomechanics of human head injury. Finite element analysis can be an important tool in describing the injury biomechanics of the human head. Complex geometric and material properties pose challenges to FE modelling. Various assumptions and simplifications are made in model development that require experimental validation. More recent models incorporate anatomic details with higher precision. The cervical vertebral column and spinal cord a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(62 citation statements)
references
References 16 publications
0
60
0
2
Order By: Relevance
“…An excellent set of reviews details the early development of these models, which focused on modeling impact testing in human surrogates and developing estimates of tolerance under simple impact conditions [119,120]. These models quickly expanded into efforts for modeling the brain mechanical response under more complex conditions, and the need to accurately model the structure, material properties, and developing new material formulations for the soft brain material properties became evident.…”
Section: An Integrated Multiscale Approach For Understanding Traumatmentioning
confidence: 99%
“…An excellent set of reviews details the early development of these models, which focused on modeling impact testing in human surrogates and developing estimates of tolerance under simple impact conditions [119,120]. These models quickly expanded into efforts for modeling the brain mechanical response under more complex conditions, and the need to accurately model the structure, material properties, and developing new material formulations for the soft brain material properties became evident.…”
Section: An Integrated Multiscale Approach For Understanding Traumatmentioning
confidence: 99%
“…That work concluded that there exists higher shear strain for windshield impact compared with A-pillar impact. Khalil and Viano [21] and Voo et al, [22] have reviewed these older models. More recently, Claessens [23] constructed a model and used it for parametric tests.…”
Section: Introductionmentioning
confidence: 99%
“…However, finite element analysis (FEA) has become an important and effective tool to investigate the biomechanics of trauma, including brain and spine injury mechanics Voo, Kumaresan et al 1996;Wheeldon, Khouphongsy et al 2000), but there have been no published analyses of SCI mechanics.…”
Section: Discussionmentioning
confidence: 99%